Critical Analysis of Technological Intervention in the Humanitarian Crisis of Sudan and the UN Agencies Resistance - Rabbani, Humaira Surya (Program Studi Teknik Informatika Universitas Paramadina, 2025)
Sudan is a country that has been described by the UN as the worst humanitarian crisis in 2024. Technology became the tool for the human rights violations by the conflicting parties and gun for UN agencies working in Sudan to entangle the social disaster and food security by providing short term and long-term actions and solutions in many fields. The data collection in this paper was carried out using history and data analysis. The limitation of this study paper was the absence of a chance for the researcher to go directly to Sudan to get first-hand data. All data will likely be checked into reliable sources. From the results analysis data in the paper, it can be concluded that technological intervention in the human crisis has contributed and succeeded in many positive ways to being the last platform for the victims and on the contrary, being abused, and failed to open the Sudanese issue to the international community.